The peremptory nature of the principle no peace without justice with respect to those most responsible persons for crimes against humanity and the consequences for the scope of application of the so called transitional justice (2016)
This text studies the imperative nature of the prohibition of committing crimes against humanity in international law, and the obligation to prosecute, judge, and punish these crimes. In this way, it develops the complementarity of transitional justice with the abovementioned obligations. These results in the conclusion that transitional justice processes have to be built on the paradigm of “no peace without justice” and not the other way around. © 2016, Universidad Nacional Autonoma de Mexico. All rights reserved.